ESCOLARIZAÇÃO E INSERÇÃO DA PESSOA COM DEFICIÊNCIA AUDITIVA NO MERCADO DE TRABALHO FORMAL NA CIDADE DE SÃO LUÍS - Aroucha, Maria José Rabelo (2011)
Research about Schooling and the insertion of the person with hearing deficiency in the formal labor market in the city of São Luís realized in the post graduation program in Education, Master in Education, of the Federal University of Maranhão. It was determinated as research object the relation between schooling and the insertion of the person with hearing deficiency in the formal labor market in the city of São Luís-MA. It presents as general objective to understand the relationship between the schooling and the insertion of the person with hearing deficiency in the formal labor market in the city of São Luís. Even in relation of this person, it has as specific objectives: to diagnose the factors which make difficult or make easy her admission and professional performance in the labor market; to identify in which professional activities she is inserted in the labor market in São Luís; to characterize the forms of work developed by her; to identify the forms of selection and contracting of private companies; to relate the professional activities developed by her with the abilities supposement acquired in her schooling process; to relate her professional activities with her professional ambitions and to reflect about her insertion process, investigated by guidance of the Politics of Inclusion in the labor market. As theoretical perspective, it was used the historical-critical approach considering the contributions of: Marx (1973, 1980, 2007, 2009); Antunes (2006, 2008); Ponce (1982); Bourdieu and Passeron ( 2008 ); Saviani (2003); Bueno (2004); Pessotti (1984); Mendes and Pereira (2009); Jannuzzi (2006); Luklin (2005); Dorziat (2009); Silva (2007), among others. The investigative focus used was the historical-critical. The subjects involved consisted in three people with hearing deficiency inserted as employees in one of the stores of a company in the city of São Luís, the coordinator of the Sector of Social Responsability of the reported company and the coordinator of the Nucleus of Insertion for work of the Center of Support and teaching of the person with deafness. As procedures, it used the documental and bibliographic re searchand the case study. At treatment and analysis of the data realized in a qualitative approach, it was used the method of analysis of contents. It points as results of this research that the communication, the fault in basic schooling of people with hearing deficiency, as well as the fault of information of the employers about laws of quota difficults the admission of people with hearing deficiency in the labor market. These people are inserted in various activities of economy and they are, in majority, in the commercial sector in the food field. The contracting happens following the requirements of the formality of the job, therefore they need the reading ability and mathematical knowledge to do tasks. It was noticed that the schooling is a process that contributes for her insertion in the labor world and that the preparation for in it insert extends to the educational process as a whole.